The role of CGIAR Germplasm Health Units in averting endemic crop diseases: the example of rice blast in Bangladesh - Enriquez, Y.; Smale, M.; Jamora, Nelissa; Hossain, M.; Kumar, P. Lava (Springer, 2022)
Background One of the less known benefits of the CGIAR is the facilitation of international agricultural research for crop improvement by providing a continuous supply of breeding materials for the development of disease resistant varieties. The Germplasm Health Units (GHUs) of the CGIAR are phytosanitary mechanisms put in place to help ensure safe (from pests and diseases) and efficient international transfer of germplasm among genebanks and breeding programs around the world. To date, there is no systematic documentation of the pathways and extent to which GHUs contribute to economic impact in recipient countries.